Protein Tyrosine Phosphatase as Potential Therapeutic Target in various Disorders - Verma, Shivani; Sharma, Saurabh (Current Molecular Pharmacology, 2018)
Background: Tyrosine-protein phosphatase is an enzyme that functions in a unit with tyrosine kinases to regulate signaling pathways. Several members of the PTP family link to human disease predisposition such as PTP1B, SH2, DEP1, and inhibition of these enzymes may represent an effective palliative therapy. Objective: This review aims to summarize the rapidly developing role of the PTPs in various physiological and pathological states. Results: Pharmacological inhibition of protein tyrosine phosphatase has been found to reduce endothelial dysfunction in different cardiovascular diseases related to metabolic disorders and it can be helpful for the management of other brain disorders associated with perhaps even in normal, agerelated cognitive decline. Tyrosine-protein phosphates have both stimulatory and inhibitory consequences on cancer-associated signaling pathways and deregulation of PTKs involves tumorgenesis. Conclusion: Inhibition of protein tyrosine phosphatase plays an important function in the improvement of various diseases such as metabolic, cardiovascular disorders, cancer and autoimmune disease.
Keywords: cardiovascular diseases